2017
DOI: 10.1136/jim-2017-000566
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Profiling of Acute Myeloid Leukemia with Normal Cytogenetics in Brazilian Patients: The Value of Next-Generation Sequencing for Genomic Classification

Abstract: Karyotype (KT) aberrations are important prognostic factors for acute myeloid leukemia (AML); however, around 50% of cases present normal results. Single nucleotide polymorphism array can detect chromosomal gains, losses or uniparental disomy that are invisible to KT, thus improving patients' risk assessment. However, when both tests are normal, important driver mutations can be detected by the use of next-generation sequencing (NGS). Fourteen adult patients with AML with normal cytogenetics were investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…CEL files were analyzed using Chromosome Analysis Suite v3.0 (ChAS) software. Regions of copy number variations (CNVs) larger than 1 Mb and CN-LOH larger than 10 Mb identified by the ChAS Software or detected by visual inspection, regardless of gene content, are considered true aberrations, with the exception of those known to be normal genomic variants (present in the Genomic Variants Database [http://projects.tcag.ca/variation]) or identified in constitutional (buccal cells) SNPa analysis 10. Aberrations identified by SNPa were described according to the ISCN 2016.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CEL files were analyzed using Chromosome Analysis Suite v3.0 (ChAS) software. Regions of copy number variations (CNVs) larger than 1 Mb and CN-LOH larger than 10 Mb identified by the ChAS Software or detected by visual inspection, regardless of gene content, are considered true aberrations, with the exception of those known to be normal genomic variants (present in the Genomic Variants Database [http://projects.tcag.ca/variation]) or identified in constitutional (buccal cells) SNPa analysis 10. Aberrations identified by SNPa were described according to the ISCN 2016.…”
Section: Methodsmentioning
confidence: 99%
“…SNPa is a sensitive technique used to perform high-resolution genome-wide DNA copy number analysis and to detect copy-neutral loss of heterozygosity (CN-LOH). Next-generation sequencing (NGS) is capable of detecting single nucleotide variants (SNVs) or small insertions and deletions that have recently been shown as important molecular phenomena in AML 10. To substantiate this idea, we describe two JAK2 -mutated AML cases for which both SNPa and NGS added valuable information.…”
Section: Introductionmentioning
confidence: 97%
“…NGS gene panels for the diagnosis of hematologic malignancies typically assay 20-60 full-length genes and/or parts of genes containing known mutation hotspots. Some studies have focused on a single cancer type, most commonly AML, [1][2][3][4][5][6][7][8][9][10][11][12][13][14] while others have included a range of myeloid-related neoplasms. [15][16][17][18][19][20][21][22] Assays which contain a customized set of genes (and/or hotspots) have been useful on a research basis to describe the extent of myeloid mutations, 13,15,20,21,[23][24][25][26][27] while clinical testing can benefit from studies which use and validate more widely available commercial assays.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22] Assays which contain a customized set of genes (and/or hotspots) have been useful on a research basis to describe the extent of myeloid mutations, 13,15,20,21,[23][24][25][26][27] while clinical testing can benefit from studies which use and validate more widely available commercial assays. 1,2,4,[7][8][9][10][11][12]14,19,22,28,29 While the previously referenced studies examined mutations in a single gene, such as insertions, deletions, and point mutations, the study of gene fusions in hematological malignancies using NGS gene panels has been less common, and the use of gene panels that concurrently assess both single-gene variants and gene fusions even more rare. A recent study compared two commercially available RNA-based fusion panels and found that they are suitable for initial diagnosis, though their sensitivity was less than that of traditional targeted, PCR-based assays.…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis in AML patients could be further stratified by different mutation combinations and hence the value of nextgeneration sequencing for genomic classification [8]. Dimensions of constitutive activation of the FLT3-ITDs are also reflected in other tyrosine-kinase receptor type III family in a manner that wellillustrates the high levels of homology between various members of this large receptor family.…”
Section: Constitutional Activationmentioning
confidence: 99%